Cost of water for peace and the environment in Israel: An integrated approach. Issue 7 (30th July 2015) - Ward, Frank A.; Becker, Nir
Abstract This paper presents a framework for discovering an economically viable water sharing plan among neighboring communities for promoting peace and environmental protection. Its application is to the Middle East in which Israel may be facing water supply obligations to address environmental requirements and for a possible a peace agreement with its Palestinian neighbors. The framework consists of integrating external factors, constraints, policy instruments, and targets. Our findings from a constrained optimization analysis of Israel's national water system show that the costs of increased deliveries are dependent on two major issues: (1) achieving integrated water resources management (IWRM) in which efficient combinations of expansion from several supply sources and reductions in demands occur over time, and (2) the cost of desalination technologies. We identify a US 1.46 billion price tag, in present value terms, from using integrated management of demand reduction and supply expansion under current desalination costs. Adjustment costs will decline both with anticipated reductions in desalination costs and with an efficient implementation of IWRM. These adjustments can contribute to moderating regional tensions and protecting key ecological assets while addressing water scarcity in a volatile corner of the world.